TRANSFORMATION OF PUBLIC FINANCES: GENDER BUDGET - Taukesheva T.D.; Daudova G.V. (Pressing Problems of Public Administration, 2018)
The issue of gender budgeting in the context of reforming public  nances is elucidated. The resultsof gender analysis of programs and problems hindering the integration of gender budgeting in thebudget process are highlighted. The approaches to incorporating the gender component into thecompilation of state and local budgets are proposed.